A new traceable method for determination of periodic nonlinearities of interferometers - art. no. 629206 - Schmidt, Ingomar; Jäger, Gerd; Hausotte, Tino; Manske, Eberhard; Füßl, Roland (Proceedings Volume 6292, Interferometry XIII: Techniques and Analysis, 2006)
A new traceable method has been developed and investigated to experimentally determine the total amount of measuring deviations arising through the capture and demodulation of plane-mirror interferometer signals. The basic principle for such an analysis is the precise specification of length variations. However, either a measuring system of excellent accuracy or accurately defined movements within a stable platform are required. A common measuring motion can be achieved through the displacement of a reflecting wedge plate, which creates a constant step-down. The interferometer to be analyzed is used to determine the change in the wedge plate's thickness, which is caused by lateral movements controlled by another interferometer. The wedge's sampled surfaces demand high planarity as the change of thickness acts as the material measure. These conditions can be achieved by using the Nanopositioning and Nanomeasuring Machine in conjunction with a 0.5-degree tilted mirror placed on it. The interferometer to be analyzed is aligned with this mirror. To provide the highest possible linearity for lateral motion, the only measuring points are in nearly error-free lambda/2 steps of the interferometer. The NPM machine's already small deviations in positioning will only affect the evaluation of measuring errors of the reduced interferometer by a factor of about one-hundredth. This is one of the main advantages of the method. The interferometer to be analyzed - like the entire measuring setup - features a compact assembly and high mechanical and thermal stability. The measured deviations in linearity provide excellent verification of the prospected error influences.
Keywords: laser interferometer; periodic nonlinearities; cyclic errors; wedge plate; Nanopositioning and Nanomeasuring Machine